Pemahaman pelajar matrikulasi tentang logaritma - Noor Aziah, Abdul Ghani (2014)
Logarithm is a difficult topic for most students. Lacking the appropriate skills to apply logarithmic rules, a weak understanding of concepts in Logarithm and the way students are taught could cause the students to face difficulty in understanding the subject. Consequently, students‟ competence to solve logarithmic questions and their mathematics performance at higher educational levels will be affected. This study was carried out to explore and identify the issues involved in the understanding of Logarithm among Matriculation students. This study had adopted the sequential explanatory research design. A total of 138 students in the first semester 2011/2012 session of the Two-Year Matriculation Program at a Matriculation College in northern Peninsular Malaysia participated in this study. In the first phase of the study, the Student‟s Understanding of Logarithm (ToSUL) test was used to determine these students‟ achievement in Module I, II, and III Logarithm. In phase two, interviews were carried out using the interview protocol which was developed by the researcher. ToSUL was scored using the marking scheme which was developed by a group of experts. Students‟ scores for every item were recorded on a Microsoft Excel worksheet and the overall percentage scores were sorted in ascending order. The students‟ achievements in the ToSUL were categorized as “pass” or “fail” in accordance with the achievement standards set by the Matriculation Division, Ministry of Education. A total of 117 (84.78%) students failed the test. Results of the Post Hoc Gabriel test showed a significance difference in the achievement in ToSUL between Module II and Module III students. Five students were unable to provide the definition for "logarithm‟. Attention was given more to the procedures to obtain the answers instead. The inclination towards procedural and instrumental understanding of Logarithm was more prevalent. Four types of errors made were in algebra, the generalization of logarithmic rules, understanding the concept of indices, and the failure to follow the instructions about the questions. The research participants attributed three factors for their problems in using logarithmic rules, namely the instructor, the students themselves, and the questions. The instrumental or procedural understanding of Logarithm and the mismatch between teaching and learning appeared to have consequences on students‟ competence to solve logarithmic questions. This study contributes to the research findings in mathematics education and the formation of policy related to the development of mathematics education curriculum for matriculation students.